2006
DOI: 10.1111/j.1600-6143.2006.01297.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate Mofetil Reduces Intimal Thickness by Intravascular Ultrasound After Heart Transplant: Reanalysis of the Multicenter Trial

Abstract: The mycophenolate mofetil (MMF) trial involved 650 heart transplant patients from 28 centers who received MMF or azathioprine (AZA), both in combination with cyclosporine and corticosteroids. Baseline and 1-year intravascular ultrasound (IVUS) were performed in 196 patients (102 MMF and 94 AZA) with no differences between groups in IVUS results analyzed by morphometric analysis (average of 10 evenly spaced sites, without matching sites between studies). Baseline to first-year IVUS data can also be analyzed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 19 publications
1
44
0
3
Order By: Relevance
“…106 Reanalysis revealed a significant decrease in the number of patients with first-year maximal intimal thickness Ն0.3 mm (a primary end point) in the MMF group. 107 Moreover, the first-year decrease in mean lumen area and the decrease in vessel area in the azathioprine group was significantly greater than in the MMF group. 107 These results were confirmed by Kaczmarek et al, 108 who detected (using multivariate Cox regression analysis) that MMF decreased the incidence of CAV significantly (Pϭ0.041).…”
Section: Mycophenolate Mofetilmentioning
confidence: 94%
“…106 Reanalysis revealed a significant decrease in the number of patients with first-year maximal intimal thickness Ն0.3 mm (a primary end point) in the MMF group. 107 Moreover, the first-year decrease in mean lumen area and the decrease in vessel area in the azathioprine group was significantly greater than in the MMF group. 107 These results were confirmed by Kaczmarek et al, 108 who detected (using multivariate Cox regression analysis) that MMF decreased the incidence of CAV significantly (Pϭ0.041).…”
Section: Mycophenolate Mofetilmentioning
confidence: 94%
“…In the re-analysis of the same study, it also showed less intimal thickening and wider lumen area [137] . Finally, Kaczmarek et al [138] , in 2006 demonstrated that MMF decreased CAV incidence.…”
Section: Mycophenolate Mofetilmentioning
confidence: 68%
“…Purine synthesis inhibitors: A long-term follow-up study of the first randomized MMF heart study (58,59) has confirmed that the benefits associated with this agent extend to three years following transplantation, with reduced graft loss due to rejection and a 36% reduction in overall mortality. A re-analysis of the intravascular ultrasound data from this trial also showed less progression of allograft coronary artery disease (ACAD) (60).…”
Section: Maintenance Therapymentioning
confidence: 77%